REGIONAL CHANGES IN LIFE EXPECTANCY AND CAUSES OF DEATH IN MOLDOVA AFTER INDEPENDENCE - Penina, Olga (Economy and Sociology, 2022)
After the period of fluctuations related to the socio-economic crisis of the 1990s, life expectancy at birth in Moldova mainly stagnated until 2005 in females and 2010 in males. Recent trends show moderate improvements until the COVID-19 pandemic. Data and methods: regional data on mortality by cause were analysed for three five-year periods around 1993, 2004 and 2014. Differences in life expectancy at birth between the leading districts and the lagging districts were decomposed by age and cause. Results: A gradient in life expectancy was revealed between the northern districts and the municipality of Chisinau, where mortality is low, and the belt of the districts located mainly in the centre, where mortality is high. Cardiovascular and digestive diseases in both sexes, as well as external causes of death in males were responsible for the interregional mortality disparity. The recent growth in life expectancy was accompanied by an increasing interregional disparity of mortality from cardiovascular diseases among the elderly and external causes of death among the middle-aged. The most significant progress was in the municipality of Chisinau, while in the rest of the country, it mainly reflected the recovery from the severe socio-economic crisis of the 1990s. Conclusions: The districts falling within the red belt of high mortality have made no progress in terms of population health since independence. In this geographic area, preventive measures aimed at reducing the risk factors associated with cardiovascular disease, liver cirrhosis and external causes of death are needed.